Combination Therapy Of Frenectomy And Orthodontic Appliance For Midline Diastema Closure - Ulfah Chaerani Saputri; Ayu Rahayu Feblina; Surijana Mappangara (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction : Midline Diastema are a main aesthetic concern for patients, due to its location in anterior teeth and its visibility during smiling. One of the main causes for a midline diastema is an aberrant frenum position, causing the gap between the anterior teeth. In order to address the problem a frenectomy was performed, followed by the application of orthodontic appliances. Case : Patient was referred from the Orthodontic Department of Hasanuddin Dental Hospital due to relapsing Midline Diastema. Patient complained of an non-aesthetic smile due to the gap in the anterior tooth. Class IV Frenal Attachment. Mucogingival Deformities and Conditions Arounds Teeth (Aberrant Frenum/Muscle Position). Case Treatment : Patient showed full healing in 1 month and full diastema closure using Removable Orthodontic Appliances in 6 months. Discussion : Frenectomy is done  to remove the aberrant attachment and removing the frenal position that blocked in the midline area, thus removing the cause of diastema. Full closure is achieved through orthodontic appliance. Conclusion : Combination of Frenectomy and Orthodontic Treatment shows a high effectivity in treating Midline Diastema.